SOME SOOTY MOULDS AND BLACK MILDEWS FROM SINGAPORE AND THE MALAY PENINSULA - G. LIM (Reinwardtia, 1975)
In Singapore and the Malay Peninsula sooty moulds and black mildews are common. Colonies of these fungi on plant foliage often consist of several species mixed together and each species may produce more than one type of conidia and other fruiting structures. The specimens collected and examined are described and listed under Ascomycetes (17 species) and Fungi Imperfecti (16 species). The most common species were those of Meliola and Microxyphium. A host list is provided.